Esporte e mulher: o fisiculturismo feminino para além das aparências - LIMA, Jefferson Dornelas de (2022)
This work has as its theme: Sports and Women: The female bodybuilding beyond appearances, which aims to identify the main limits and difficulties of the female gender in being a bodybuilding athlete. Analyzes through the answers of athletes, what is the limit for female bodybuilding reported by athletes linked to IFBB-Pa?. The methodological approach was based on a field study research that focused on the female bodybuilding athlete community. Through a semi-structured script, prepared by the Google Forms platform and sent to fifteen (15) athletes, it was possible to collect data virtually due to the current state of the pandemic, and consisted of questions in the following axes: personal data , sports - athlete's life, conditions for training and difficulties as a woman in a mostly male sport. The result of the research was that there are two limits found by these athletes, they are: lack of sponsorship and lack of recognition/support.